Syphilis among men who have sex with men attending a large HIV clinic in Trinidad. (August 2021) - Edwards, Robert Jeffrey; John, Isshad; Todd, Selena; Lavia, Leon-Omari; Musa, David; Edwards, Jonathan; Boyce, Gregory
A chart review study was conducted to determine the prevalence of syphilis and explore the associated risk factors among men who have sex with men (MSM) who attended a large HIV clinic in Trinidad during the period January–December 2019. Patients were routinely screened for syphilis annually, and demographic, clinical, and laboratory data were extracted from the medical records. Descriptive and bivariate analyses were performed, and factors significantly associated with a syphilis diagnosis were assessed using multivariate logistic regression. During the period, 218 MSM were seen, age range 19–67 years, and median age 34.0 years. The prevalence of syphilis was 41.3% (90/218), and 71.1% (64//90) of these infections were asymptomatic. Multivariate analysis using logistic regression showed that MSM living with HIV in the 30–34 years old-age group (OR, 4.32; 95% CI, 1.04–18.02), and those with a previous history of treated syphilis (OR, 10.18; 95% CI, 4.60–22.53) were more likely to be diagnosed with syphilis. The prevalence of syphilis is high among MSM attending the HIV clinic in Trinidad, and most of these infections were asymptomatic; hence, targeted and sustained interventions to reduce syphilis transmission are urgently required. Repeat episodes of syphilis may play a role in the transmission dynamics of syphilis in MSM.